1999
DOI: 10.1063/1.125372
|View full text |Cite
|
Sign up to set email alerts
|

Gain characteristics of InAs/GaAs self-organized quantum-dot lasers

Abstract: We report a study of the gain characteristics of a self-organized InAs/GaAs quantum-dot laser. Using the Hakki–Paoli technique, we are able to determine the spectral form of the modal gain, its dependence upon current, and the differential gain. A quasiperiodic modulation of the below-threshold gain is observed. This modulation is shown to be responsible for the form of the lasing spectra, which consist of groups of lasing modes separated by nonlasing spectral regions. Possible mechanisms for this behavior are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Self-assembled semiconductor quantum dots (QDs) grown by Stranski-Krastanov mode have emerged as an attractive subject in terms of fundamental physics and potential device application [1,2]. It has been theoretically predicted that the device performances would be greatly enhanced by adopting QDs as an active medium [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled semiconductor quantum dots (QDs) grown by Stranski-Krastanov mode have emerged as an attractive subject in terms of fundamental physics and potential device application [1,2]. It has been theoretically predicted that the device performances would be greatly enhanced by adopting QDs as an active medium [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This can even prohibit lasing from the ground state in some QD structures. [3][4][5] Previous theoretical studies 6,7 suggested that the low gain arises because the built-in piezoelectric field leads to the ground state hole wave function being elongated, with the matrix element then reduced due to lower overlap between the electron and hole wave functions. We show here that this is not the only reason for low optical matrix element.…”
mentioning
confidence: 99%
“…In Refs. [7,14,15] and [10] values of about 12, 2.5, 11 and 8 cm --1 per sheet, respectively, were reported. The electroluminescence (EL) spectra are taken from the first section (100 mm), for the lowest and the highest injection current density as indicated.…”
mentioning
confidence: 89%